Anti‐cholinesterase and antioxidant properties of alkaloid and phenolic‐rich extracts from pawpaw (Carica papaya) leaf: A comparative study. (1st September 2020) - Adedayo, Bukola C.; Oyeleye, Sunday I.; Okeke, Bathlomew M.; Oboh, Ganiyu
Abstract: Carica papaya, commonly known as pawpaw, is a tropical plant cultivated for its edible ripe fruits. However, its leaf is being use traditionally against several life‐threatening illnesses, including Alzheimer disease (AD). This study compared the cholinesterases (ChEs) inhibitory effect and antioxidant property of alkaloid and phenolic [aqueous, acetone and methanol‐HCL (0.1:50 w/v)] rich extracts of Pawpaw leaf. The extracts were prepared to the concentration of 2 mg/mL, thereafter, effect on ChEs [acetylcholinesterase (AChE) and butyrylcholinesterase (BChE)] activities, and production of quinolone (QA) and Fe‐induced thiobarbituric reactive acid species (TBARS)] as well as antioxidant [ferric reducing antioxidant property (FRAP), 2, 2‐diphenyl‐1‐ picrylhydrazyl (DPPH) radical scavenging ability] properties were determined. Total phenol and flavonoid contents of the phenolic‐rich extracts, as well as gas chromatography analysis of an alkaloid extract, were carried out. Results revealed that hydromethanolic extract had the highest AChE inhibitory effect while aqueous extract had the highest BChE inhibitory potential. Hydromethanolic extract demonstrated highest inhibitory effect on Fe 2+ ‐induced TBARS production, while alkaloid extract had strong inhibition on QA‐induced TBARS production. Aqueous extract had the highest total phenol content, while hydromethanolic extract had the highest total flavonoid content. All the extract exhibited anticholinesterases and antioxidant properties, however, hydromethanolic extract appears to be the most potent and could be as a result of its rich flavonoid content. The biological properties of the studied extract could be the underlying neuromodulatory mechanism of actions of pawpaw leaf in folklore against some neurological disorders. Abstract : Anti‐chilinesterase and antioxidant Properties of pawpaw leaf extracts.